2021
DOI: 10.1038/s41415-020-2499-1
|View full text |Cite
|
Sign up to set email alerts
|

Dental emergencies presenting to maxillofacial units during the COVID-19 pandemic: a five-centre UK hospital study

Abstract: Access to emergency dental care was unpredictable and significantly limited, particularly during the beginning of the COVID-19 pandemic period.A proportion of patients with dental emergencies attended hospital emergency services with nowhere else to turn, often with more severe symptoms than normally encountered, having had no treatment and often multiple antibiotic courses.Treatment of patients in a dental setting during the pandemic period was challenging due to transmission risk factors and aerosol generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
1
8
0
1
Order By: Relevance
“…Out-patient services began in May, 2020. Approximately the same proportions of male and female reported in the OPD (52.8% v/s 47.2) which is in accordance with the study of Haquin Guo [12] et al, AM Kranz [13] et al, Pajpani et al [14] and Kristian Blackhall [15] et al…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Out-patient services began in May, 2020. Approximately the same proportions of male and female reported in the OPD (52.8% v/s 47.2) which is in accordance with the study of Haquin Guo [12] et al, AM Kranz [13] et al, Pajpani et al [14] and Kristian Blackhall [15] et al…”
Section: Discussionsupporting
confidence: 89%
“…The proportions of patients seeking emergency dental care due to abscess/ swelling /space infection are 3.4% and those reporting due to trauma/ fracture are 2.3%. The observations in previous studies show a much higher range [12,14,15,20] . Emergency services like extraction (29%) of the teeth causing pain, sutures/ intermaxillary fixations (7.9%) in case of orofacial trauma and pulpectomies (21%) were the main treatment provided in the Departments of Oral and Maxillofacial Surgery, Endodontic and Pedodontic.…”
Section: Discussionmentioning
confidence: 69%
“…These studies have focused on processes implemented to operationalise UDCs and on their clinical activity and output. 13,14,15 To date, no published study has explored and reported frontline experiences of what it was actually like to work within a UDC and why. This is surprising considering the long-term impact of COVID-19 and UDC operations on dentistry, the richness of lessons potentially learnt from this time and the high likelihood that processes, such as the ones used during COVID-19, will be required in the future again.…”
Section: Introductionmentioning
confidence: 99%
“…To date, there have been numerous studies investigating the effect of the fear of contamination, stay-at-home orders, and lockdown measures that emerged with the pandemic in 2020 on admissions due to urgent or non-urgent clinical conditions other than COVID-19 (12-14). Additionally, the reasons and numbers of dental emergencies presenting to various dentistry departments during the COVID-19 pandemic have also been investigated [ 6 , 10 , 15 ]. However, to our knowledge, there has been no study specifically investigating admissions due to non-urgent dental or orthodontic treatment.…”
Section: Introductionmentioning
confidence: 99%